Pemilu Bersih Antara Harapan dan Kenyataan - Maliki, Moh. (LPPM Universitas Putera Batam, 2024)
Elections are a celebration of people's democracy which should be conducted honestly and openly. The main purpose of elections is to find leaders who are able to improve the conditions of society, especially for those who have difficulty meeting the necessities of life for themselves and their families. Elections are expected to be a path for Indonesian citizens towards prosperity, as mandated by the 1945 Constitution. However, in reality, elections are still characterized by various difficult challenges that must be faced by all Indonesian people. One of them is the existence of fraudulent practices that are difficult for the state to fully control, in this case election organizers. This fraudulent practice occurs among all parties, organizers, voters and election participants. They are intertwined with each other. Public apathy towards holding elections is one of the reasons. Another reason is the massive practice of money politics that occurs. The need for money in society is still very high, so the risk of manipulation by the power of money in elections is a reality that must be taken seriously for the future of Indonesian democracy. However, the success of the election is a success for Indonesian democracy. As a sovereign country, elections are a way for Indonesia to achieve the ideals of prosperity for all its people.